Atlas of Fallen Dust in Kuwait - Al-Dousari, Ali; Al-Dousari, Ali (Springer Nature, 2021)
This open access book serves as an atlas of deposited dust and dust storms in Kuwait in relation to local and global regions. It features a wealth of maps and images of dust storm trajectories in the region, together with detailed descriptions of the chemical and physical properties of fallen dust, including the amount, particle size, statistical parameters, spectra absorption, dust mineralogy, trace and major elements, organic matter, associated pollen, and radionuclides and connected pollutants. Given its scope, the book is a valuable resource for a broad range of researchers, including geologists, chemists, environmentalists, botanists, air quality specialists, nanotechnology scientists, and solar energy experts.
English
Keywords: Pollution & threats to the environment; Human geography; Earth sciences; Analytical chemistry; Meteorology & climatology; Atmospheric Protection/Air Quality Control/Air Pollution; Medical Geography; Atmospheric Sciences; Analytical Chemistry; Climatology; Environmental Sciences; Medical/Health Geography; Earth System Sciences; Aeolian Dust; Dust Storms Trajectories; Land Degradation an Desertification; Radiunoclides, Pollen; Chemical and Physical Properties of Dust; Dust in Kuwait; Open Access; Pollution & threats to the environment; Human geography; Epidemiology & medical statistics; Earth sciences; Meteorology & climatology